Continuity and Discontinuity of National Roles in Middle-Power States: The Case of Indonesia’s Foreign Policy - Abubakar Eby Hara (Universitas Islam Internasional Indonesia (UIII), 2025)
This paper examines the continuity and discontinuity of national roles adopted by middle-power states, with Indonesia as a case study. It focuses on two auxiliary roles linked to Indonesia’s master role as a regional leader. The first is Indonesia’s role as a promoter of democracy through the Bali Democracy Forum, a role that continued from the administration of Susilo Bambang Yudhoyono (2004-2014) to that of Joko ‘Jokowi’ Widodo (2014-2024). The second is Indonesia’s role in constructing a maritime cooperation framework under the Global Maritime Fulcrum policy initiated during Widodo’s first term, but which saw discontinuation in his second term. This paper seeks to explain why one auxiliary role persisted while the other did not. Drawing on national role conception theory, particularly the distinction between master and auxiliary roles, it argues that the sustainability of auxiliary roles depends not only on external expectations aligned with the master role, but also on internal legitimacy and support. In the case of the Global Maritime Fulcrum policy, strong domestic contestation undermined the auxiliary role, despite its alignment with Indonesia’s regional leadership ambitions.